Application of different compost doses in Pinova and Golden Delicious apple orchards - Szabó, Anita (Acta Agraria Debreceniensis, 2013)
Nowadays the success vegetable and fruit production are unimaginable without regular nutrient management. The animal husbandry is getting decrease, thereby there is the lack of organic fertilizer and it is suggested to find alternative nutrient supply methods. One of the ways to supply the required nutrients in an environmentally friendly way is the application of composts, which is less widespread so far, which is appropriate for the requirement of organic farming.From the year of 2010 in each year, compost doses were applied in biological apple orchards in cooperation with the Institute of Horticultural Science. In the function of the years different changes were resulted by the compost treatments in the examined parameters in case of both apple species (Golden Delicious and Pinova). It was concluded that the dry matter, ash, total acids, sugar content and the vitamin C changed versus time and species. It is supposed that the effect of compost treatments is getting visible.According to the data higher dry matter, total acids and sugar content, (in some cases) ash were measured in case of the apple species Pinova, while the measurements showed higher vitamin C content in case of the species Golden Delicious.